Factors Influencing Contractor Performance In Jonge Lake Road Construction Work, Malang City - Teguh Prasetijo, Christiawan; Teki Tjendani, Hanie; Witjaksana, Budi (Devotion : Journal of Research and Community Service, 2023)
The contractor is very instrumental in the success of a project. Therefore, contractors are required to have maximum performance in carrying out their work. There are various factors that affect the performance of contractors such as Human Resources, Money, Field Management, Communication, Materials and Equipment. This study aims to analyze the relationship between factors that influence contractor performance. This research is quantitative with data collection techniques in the form of interviews and distributing questionnaires. The research population consisted of 78 supervisory consultants for the Danau Jonge road construction project in Malang , with the total sample being the entire population. The research data analysis technique uses the PLS SEM method. Research proves that Human Resource and Money have a positive and not significant effect on Contractor Performance. Field Management has a negative and insignificant effect on Contractor Performance. While Communication, Materials and Equipment have a significant positive effect on Contractor Performance.